Aspectos funcionais, morfológicos e imunohistoquímicos do músculo quadríceps femoral de indivíduos com graus I ou II de osteoartrite de joelho - Serrão, Paula Regina Mendes da Silva (2012)
The quadriceps muscle weakness is common in subjects with knee osteoarthritis (OA), leading to functional deficits. Some risk factors are causes, such as morphological changes (atrophy and reduced number of muscle fibers), changes in non-contractile proteins of muscle and changes in the level of muscle activation. However, these factors are not well understood, particularly with respect if they are already present in earlier stages of the disease. Therefore, the aim of this study was to verify if men with early degrees of knee OA have functional and morphological impairments and immunohistochemical changes of the quadriceps muscle, as well as investigate if this subjects had compromising of their quality of life . The men (40-65 years) who participated in this study were divided into two groups: Control Group (CG) with healthy subjects and Osteoarthritis Group (OAG) with individuals with knee OA grade I or II. A biopsy of the vastus lateralis (VL) was performed for morphological (through the ATPase reaction) and immunohistochemical analysis(analysis of expression and localization of the receptor for advanced glycation end products - RAGE, and analysis of the expression of collagen type I and III ) . An evaluation of knee extensor torque (KET), concentric and eccentric at 90°/s and 180°/s, was performed simultaneously with an evaluation of the electromyographic activity of the VL (RMS value). Moreover, the WOMAC questionnaire was used. For the intergroup analysis, we used the independent t-test and the Mann-Whitney U test. Spearman s correlation coefficient was used to detect the relationship between the three subscales of WOMAC questionnaire and the average knee extensor peak torque (α<0.05). The collagen was analyzed by semiquantitative analysis. We found lower values for the GOA in eccentric knee extensor peak torque at 90 °/s (p = 0.01) and 180°/s (p = 0.04), and in electromyography activity (RMS) during eccentric contraction, in two angular velocities (p <0.01). Higher values were found for the GOA in the proportion (p = 0.03) and in the relative crosssectional area of type 2b fibers (p = 0.02). It was found a negative correlation between the concentric and eccentric knee extensor torque and the three subscales of the WOMAC questionnaire (p<0.05). In the analysis of RAGE no difference was found between the groups. In semiquantitative analysis of collagen was found increased expression of collagen type I and type III for the GOA. Thus, men with knee OA grades I or II present functional, morphological and immunohistochemical changes of the quadriceps muscle, indicating possible neuromuscular adaptations. Therefore, in the early stages of knee OA, exercises should be recommended in order to minimize or delay the functional deficits resulting from OA.